A note on the effect of concerts on the behaviour of Domestic dogs Canis lupus familiaris at Taronga Zoo, Sydney. Issue 1 (23rd October 2016) - Meade, J.; Formella, I.; Melfi, V.
Abstract : Loud or aversive noise is a key factor that may stress animals in zoological institutions. Many zoos host concerts in their grounds, and this practice is likely to expose resident animals to loud noises. Few studies have explored the effect of concerts and events on animals in zoological institutions. Here, the behaviour of two Domestic dogs Canis lupus familiaris at Taronga Zoo, Sydney, Australia, was compared between evenings with and without concerts. Behaviours such as whining, shaking, panting and destructive behaviour, thought to reflect fear or anxiety, occurred at low levels. Hiding can also be linked to fear and anxiety but is less easy to identify; for example, time spent in kennels could be considered hiding or resting. To examine this, the proportion of time the dogs spent inside their kennels was compared between evenings with concerts and those without. No difference was found between the two conditions. This indicates that dogs were probably resting rather than 'hiding' inside their kennels; as this behaviour made up similar proportions of evenings with and without concerts. No behaviours that may be linked to anxiety caused by concerts were identified. More comprehensive research will be carried out to explore the effect on resident animals of concerts and events held at zoological institutions. Abstract : The impact of concerts on resident animals in zoological institutions is very under researched. In a pilot study we investigated the behaviour of two Domestic dogs Canis lupus familiaris on evenings with and without concerts at Taronga Zoo, Sydney, Australia, and found no behavioural differences. (Photo: Rick Stevens, Rick Stevens Photography)